President’s Message: Dialogue With ORNAC - Hay, Vija (Operating Room Nurses Association of Canada Journal, 1996)
In my previous President’s Message I wrote about the National Conference in 1997, and the opportunity for delegates to dialogue with ORNAC Board of Directors. I want to elaborate on this topic.